Preparation and characterization of hydroquinone based polyoxalate and its application in the removal of heavy metals from water (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Hydroquinone based polyoxalate was synthesized from oxalyl chloride and hydroquinone. The polymer was characterized with FTIR, 1H-NMR, 13C-NMR, PXRD, SEM and thermal analysis. The chelation behaviour of the polymer towards Pb(II), Cd(II), and Hg(II) in aqueous solutions was studied by batch technique as a function of contact time and pH. The polymer showed high metal uptake toward Pb(II) and Cd(II) and moderate metal uptake toward Hg(II). The adsorption capacity was not affected by the pH of solution. The adsorption data were fitted with second order kinetic model and the isotherms models of Langmuir and Freundlich. Thermodynamics measurements showed that sorption process was spontaneous. Furthermore, the chelating polymer was loaded with metal ions using fixed bed column. For regenerating the loaded polymer, different eluting agents include HNO3, H2SO4, and EDTA was investigated. The highest recovery of metal ions was achieved using HNO3, indicating that desorption process was governed by the solubility factor and cation exchange mechanism.Â